Strengthening smallholder agriculture is essential to defend food and nutrition security and rural livelihoods in Myanmar against the COVID-19 threat: Elements for a proactive response - Boughton, Duncan; Goeb, Joseph; Lambrecht, Isabel B.; Mather, David; Headey, Derek D. (International Food Policy Research Institute, 2020)
There is an urgent need to anticipate and mitigate the threat posed by COVID-19 to Myanmar’s agricultural sector and to rural households that depend on farming for income and for food and nutrition security. We evaluate options to address the threat and to support farmers to prepare their land and plant their crops on time in the short window before the start of the 2020 monsoon cropping season. Recognizing that no single intervention can address the full range of vulnerabilities faced by rural households, we recommend a combination: • Expansion of access to seasonal farm credit with extended loan repayment schedules; • Limited agricultural input subsidies targeting certified seed; and • Implementation of a cash transfer program to smallholder farmers. Despite the high cost of a cash transfer program, there are good reasons to expect that the benefits of such support to farm households will outweigh program costs in monetary terms – even more so if the economic benefits from the consequent lower incidence of malnutrition to which the program would contribute can be measured.